TEXTBOOK - AN IMPORTANT ELEMENT IN THE TEACHING PROCESS - Dragana M. Gak (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2011)
The textbook plays an important role in teaching and learning. It represents a useful resource for both teachers as a course designers and learners as persons who are acquiring the English language. However, the use of a ready-made textbook has its advantages and disadvantages. This paper aims at investigating the benefits and hindrances in using a ready-made textbook as well as ways of textbook adaptation. Textbook adaptation is a process of overcoming problems in using only ready-made textbooks. Textbook adaptations at activity level, unit level and syllabus level are an integral part of the course-developing process which assists the teacher in meeting the learners' specific work-related needs.